Pengelolaan Media Pembelajaran SD Studi Situs: SD Negeri 12 Sragen - Sawarti, Sri (2011)
The aims of this research are to describe: 1. characteristic of the instruments of study in SD Negeri 12 Sragen. 2. Characteristic of using instruments of study in SD Negeri 12 Sragen. 3. Characteristic of the instruments maintenance of study in SD Negeri 12 Sragen. This study used descriptive qualitative method by ethnography design. Data were collected by observation, documentation, and indepth interview. The data were analyzed by using qualitative analysis method interactive model. The results of this study shows: 1. The study instruments of SD can be divided into three parts, there are electronics instruments, non-electronics instruments and instruments of SD teachers' works. 2. The process of supply and maintenance instruments of study of SD is from three sources, there are: 1. helping of center and region government by DAK fund allocation, 2. buying by BOS fund and, 3. buying from parents help by school committee. At the beginning of study years, school arranged budget scheme school plan, one of them is about the instruments of study. After the budget arranged, it discussed by the member of school committee and school to do anything that needed in order to increase quality of study in school. After get agreement, the school committee invites the parents to discuss about budget scheme school plan, because without supports from parents, the school budgets are not sufficed. 3. The using of study instruments of SD are scheduled in using computer instruments, whereas in using non-computer instruments are compatible with the class needed. The teacher or everyone that using the instruments should filled the book in order to prevent the destruction. The instruments of study are important in the teaching and learning process and the using of that are helping. Because when use the instruments of study, the students will be more interest and ardent to do the experiment so it can stimulate the students spirit to study and it can raising the result of study. For the teacher that cannot using the instruments are needed the training and upgrading so that all teacher free using the instruments.